Roles of the Mitotic Inhibitors Wee1 and Mik1 in the G(2) DNA Damage and Replication Checkpoints - Rhind, Nicholas (American Society for Microbiology, 2001)
The G(2) DNA damage and DNA replication checkpoints in many organisms act through the inhibitory phosphorylation of Cdc2 on tyrosine-15. This phosphorylation is catalyzed by the Wee1/Mik1 family of kinases. However, the in vivo role of these kinases in checkpoint regulation has been unclear. We show that, in the fission yeast Schizosaccharomyces pombe, Mik1 is a target of both checkpoints and that the regulation of Mik1 is, on its own, sufficient to delay mitosis in response to the checkpoints. Mik1 appears to have two roles in the DNA damage checkpoint; one in the establishment of the checkpoint and another in its maintenance. In contrast, Wee1 does not appear to be involved in the establishment of either checkpoint.